2019
DOI: 10.1371/journal.pone.0212545
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of linear model and artificial neural network using antler beam diameter and length of white-tailed deer (Odocoileus virginianus) dataset

Abstract: Evaluation of harvest data remains one of the most important sources of information in the development of strategies to manage regional populations of white-tailed deer. While descriptive statistics and simple linear models are utilized extensively, the use of artificial neural networks for this type of data analyses is unexplored. Linear model was compared to Artificial Neural Networks (ANN) models with Levenberg–Marquardt (L-M), Bayesian Regularization (BR) and Scaled Conjugate Gradient (SCG) learning algori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Through a comparative analysis of the three training algorithms, it is evident that the LM algorithm outperforms the BR and SCG algorithms. Nevertheless, both the BR and SCG algorithms still exhibit somewhat satisfactory results, although their results are not the best [12,49,50]. These results are further explained in Figure 4 for the LM algorithm.…”
Section: Results Obtained Using K-fold Cross Validation Methodsmentioning
confidence: 84%
“…Through a comparative analysis of the three training algorithms, it is evident that the LM algorithm outperforms the BR and SCG algorithms. Nevertheless, both the BR and SCG algorithms still exhibit somewhat satisfactory results, although their results are not the best [12,49,50]. These results are further explained in Figure 4 for the LM algorithm.…”
Section: Results Obtained Using K-fold Cross Validation Methodsmentioning
confidence: 84%
“…Among these, BRNN produced the most accurate outputs and always yielded a sigmoid-shaped function. The BRNN method generally performs well in comparative studies (Kayri 2016, Fikret Kurnaz and Kaya 2018, Peters et al 2019) and has been shown to be suitable for many ecological and environmental applications, such as tree height modelling (Skudnik and Jevšenak 2022), estimation of corn biomass from remote sensing data (Geng et al 2021) and interpolation of missing aerosol data (Chen et al 2020).…”
Section: Introductionmentioning
confidence: 99%